2021
DOI: 10.33192/smj.2021.96
|View full text |Cite
|
Sign up to set email alerts
|

Speech Outcome Analysis after Primary Cleft Palate Repair: Interim Siriraj Hospital Audit

Abstract: Objective: To evaluate the speech outcomes after primary cleft palate repair in a single tertiary medical institution of Thailand.Materials and Methods: A prospective cohort study was performed. Patients who had cleft palate with/without cleft lip and underwent primary cleft palate repair were included. Speech assessment was performed using the Pittsburgh weighted speech score (PWSS) by a speech-language pathologist.Results: Forty patients (21 males and 19 females) who underwent primary cleft palate repair at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Several other studies have also reported score distributions with a similar skew to our sample and lower mean scores for PWSS "articulation" measurement. 33,34 Most studies using the PWSS report total scores (not scores from subcomponents). Total scores typically demonstrate a normal distribution among cleft patients, whereas the individual components of the scale may not demonstrate a normal distribution.…”
Section: Pcc Is An Adequate Measure Of Overall Articulatory Functionmentioning
confidence: 99%
“…Several other studies have also reported score distributions with a similar skew to our sample and lower mean scores for PWSS "articulation" measurement. 33,34 Most studies using the PWSS report total scores (not scores from subcomponents). Total scores typically demonstrate a normal distribution among cleft patients, whereas the individual components of the scale may not demonstrate a normal distribution.…”
Section: Pcc Is An Adequate Measure Of Overall Articulatory Functionmentioning
confidence: 99%
“…1,2 Patients with CL/P typically require comprehensive multidisciplinary team care and long-term follow-up. 3 The principal aims of cleft care are to achieve the best quality of life in terms of function, esthetics, and psychosocial status. In the inceptive era of plastic and reconstructive surgery, "good esthetics" results from surgeons' perspectives might not match patients' perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to mortality risk, the maternal complications of HDP include pulmonary edema, myocardial infarction, stroke, coagulopathy, and renal failure. 3 There is evidence [4][5][6][7][8] and biological plausibility (i.e., imbalance of angiogenic factors and coagulopathy, [9][10][11] prolonged induction of labor due to preterm pregnancies, and use of magnesium sulfate [MgSO 4 ]-a medication associated with smooth muscle relaxation and potentially uterine atony 12,13 ) suggesting that individuals with HDP are more likely to have postpartum hemorrhage (PPH), defined as blood loss of 1,000 mL or more within 24 hours of delivery. 14 However, the current American College of Obstetricians and Gynecologists (ACOG) practice bulletin on gestational hypertension (gHTN) and preeclampsia does not acknowledge this assoication.…”
mentioning
confidence: 99%
“…First, the majority of published reports do not specify whether the association of HDP with PPH involves all cases of HDP, including chronic hypertension (cHTN), gHTN, and preeclampsia without severe features or if it is limited to only preeclampsia with severe features. 5,[17][18][19][20][21][22] Second, there are inconsistencies in the definitions of both HDP and PPH, with many publications not following contemporary ACOG guidelines. 5,11,21,23 Third, the majority of reports are from abroad, and findings may not be applicable to the United States.…”
mentioning
confidence: 99%
See 1 more Smart Citation